PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DATABASE KOMPONEN LISTRIK - Arif Harun Nadzar; Edy Supriyadi (JPTE FT UNY, 2020)
ABSTRACT:The purpose of this study were: (1) to develop Android-based learning media to assist the learning process of class X students of Electrical Power Installation Engineering also called TITL, (2) to determine the feasibility of learning media based on material and media aspects, (3) to determine the user's response to learning media. This is a research and development with the ADDIE model. The media feasibility test uses expert judgment. This research was implemented in vocational school at SMK N 1 Pundong. The research subjects were 38 students of class X TITL. The assessment instrument uses a questionnaire with a Likert scale of four choices. The data analysis technique used descriptive analysis. The results of this research and development were: (1) the product in the form of an android application